Dementia, Comorbidity, and Physical Function in the Program of All-Inclusive Care for the Elderly. Issue 2 (April 2019) - Falvey, Jason R.; Gustavson, Allison M.; Price, Lisa; Papazian, Lucine; Stevens-Lapsley, Jennifer E.
Abstract : Background: Participants in the Program of All-Inclusive Care for the Elderly (PACE) are a unique clinical population of medically complex and highly disabled older adults who qualify for nursing home level care but receive services in the community. A main goal of PACE programs is to prevent further declines in physical function that may necessitate costly institutionalization. This study evaluates how multimorbidity and dementia impact both self-selected gait speed and Timed Up and Go (TUG) in this population. Methods: This study was a cross-sectional design. Sociodemographic information, physical function, comorbidity data, and dementia status on 525 PACE participants were extracted from a quality improvement database. Separate univariable and multivariable linear regression models were used to evaluate the impact of comorbidity status and dementia on gait speed and TUG time. Results: PACE participants overall have a high degree of functional disability, with an average gait speed of 0.66 m/s, an average Short Physical Performance Battery score of 6.0/12, and an average TUG time of nearly 20 s. In the univariable analysis, a higher number of comorbidities and a diagnosis of dementia were associated with greater limitation for gait speed and TUG time. After adjusting for age, sex, strength, and balance, each additional comorbidity was independently associated with 0.015 m/s slower gait speed, as well as a 3.5% increase in TUG time for PACE participants with dementia. Conclusions: Ambulatory PACE participants have average levels of physical function that are dangerously close to thresholds thought to indicate vulnerability for further disability development, hospitalization, and nursing home admission. Both dementia and comorbidity burden are associated with declines in physical function, and the interaction between these risk factors is a telling indicator to functional decline in higher-level ambulatory tasks. PACE program clinicians can use this information to better identify participants at risk for limited physical function. Further research should investigate consequences of functional decline and determine optimal intervention strategies for PACE participants with functional impairments.